Recognizing the Role of Language in the Hidden Curriculum of Undergraduate Medical Education: Implications for Equity in Medical Training. (25th May 2021) - Wong, Bonnie O.; Blythe, Jacob A.; Batten, Jason N.; Turner, Brandon E.; Lau, James N.; Hosamani, Poonam; Hanks, William F.; Magnus, David
Abstract : Medical education involves a transition from "outsider" to "insider" status, which entails both rigorous formal training and an inculturation of values and norms via a hidden curriculum. Within this transition, the ability to "talk the talk" designates an individual as an insider, and learning to talk this talk is a key component of professional socialization. This Article uses the framework of "patterns of medical language" to explore the role of language in the hidden curriculum of medical education, exploring how students must learn to recognize and participate fluently within patterns of medical language to be acknowledged and evaluated as competent trainees. The authors illustrate this by reframing the Association of American Medical Colleges' Core Entrustable Professional Activities for Entering Residency as a series of overlapping patterns of medical language that students are expected to master before residency. The authors propose that many of these patterns of medical language are learned through trial and error, taught via a hidden curriculum rather than through explicit instruction. Medical students come from increasingly diverse backgrounds and therefore begin medical training further from or closer to insider status. Thus, evaluative practices based on patterns of medical language, which are not explicitly taught, may exacerbate and perpetuate existing inequities in medical education. This Article aims to bring awareness to the importance of medical language within the hidden curriculum of medical education, to the role of medical language as a marker of insider status, and to the centrality of medical language in evaluative practices. The authors conclude by offering possible approaches to ameliorate the inequities that may exist due to current evaluative practices.